THE DEVELOPMENT OF THE DETECTIVE GENRE IN ENGLISH LITERATURE (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The detective genre occupies a significant place in English literature and has undergone a long process of development from the nineteenth century to the present day. This article examines the historical evolution of the detective genre, its major stages, thematic characteristics, and stylistic features. Particular attention is given to the works of key writers who shaped the genre, including Edgar Allan Poe, Arthur Conan Doyle, Agatha Christie, and later modern authors. The study also highlights the structural elements of detective fiction, such as mystery, investigation, logical reasoning, and the revelation of truth. The analysis demonstrates that the detective genre reflects social changes, cultural values, and readers’ fascination with intellectual problem-solving.